PENGGUNAAN SARANA NON PENAL DALAM PENANGGULANGAN TINDAK PIDANA PENCABULAN TERHADAP ANAK DI WILAYAH HUKUM KEPOLISIAN SEKTOR TAMBANG - Fauziah Aznur; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The growing problem of the criminality is a part of social change and not a new thing of this world, even though the time and place different but still the value of its crime is the same. Crime, in addition to a humanity problem is a social problem. One of them is the crime of sexual abuse against children. According to data the authors obtained, the crime of sexual abuse against children that occurred in the police sector of Tambang has increased from year to year, it can not be avoided simply by using jaur, therefore prevention and control of this crime should be done with an integral approach, by using non penal facility. The purpose of this thesis, First, to determine the factors that cause criminal acts of sexual abuse against children in Jurisdiction Police Sector of Tambang, Second, the use of non penal facility in the prevention of criminal acts of sexual abuse against children in Jurisdiction Police sector of Tambang, Third, to know the obstacles of using non penal facility for tackling felony obscenity against children in police sector of Tambang.This type of research is a sociological study, the research wanted to see the correlation between law and society, so as to reveal the effectiveness of the rule of law in society and to identify the unwritten law that applies to communities.From the results of research and discussion of the problem, it can be concluded, First, the factors that caused the criminal offense of sexual abuse against children in police sector of Tambang is the lack of parental supervision, lack of education and the economy, technology and the mass media. Second, the use of non penal facility in the prevention of criminal acts of sexual abuse against children in police sector of Tambang was not effective yet.Third, the barriers faced by the limited number of members of the police, lack of community participation, law enforcement officers are less professional in their duties and functions, and lack of facilities and infrastructure. Suggestions Writer, First, to the relevant parties can address the factors that cause criminal acts of sexual abuse against children in a way to make people aware that child protection is everyone's responsibility, namely through the use of non penal facility, Second, because most of time, children are victims of felony obscenity in police sector of Tambang, the police sector of Tambang need to make effective use of non penal facility in response for sexual abuse against children by conducting legal counseling, Third, government / local governments can support the use of non penal facility with complementary facilities and infrastructure the necessary legal authorities in carrying out its duties and functions. And to the law enforcement authorities in order to enhance professionalism in performing their duties in accordance with their each field, for the purpose of law can be achieved as appropriate.Keywords: Non- Penal Facility, Obscenity Crime, Children